2004
DOI: 10.1038/sj.npp.1300626
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Improvement in Schizophrenic Patients does not Require a Serotonergic Mechanism: Randomized Controlled Trial of Olanzapine vs Amisulpride

Abstract: Combined serotonin-2A (5-HT 2A ) and dopamine-2 (D 2 ) receptor blockade has been proposed as a candidate mechanism by which second-generation antipsychotics (SGAs) improve both cognition and negative symptoms in schizophrenic patients, in contrast to antipsychotics of the first generation. The SGA amisulpride, however, only binds to D 2 /D 3 receptors, which makes it an interesting tool to test this assumption. In a randomized controlled trial, 52 schizophrenic patients were allocated to treatment with either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 58 publications
5
32
1
2
Order By: Relevance
“…APD, has also been reported to improve cognition allegedly by a nonserotonergic mechanism (Wagner et al, 2005). The development of novel adjunctive or stand-alone treatments that can improve some domains of cognition in schizophrenia, accompanied by functional improvement, is a major goal of pharmacologic research (Buchanan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…APD, has also been reported to improve cognition allegedly by a nonserotonergic mechanism (Wagner et al, 2005). The development of novel adjunctive or stand-alone treatments that can improve some domains of cognition in schizophrenia, accompanied by functional improvement, is a major goal of pharmacologic research (Buchanan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Wagner et al reported that the atypical antipsychotic amisulpride (which is devoid of 5HT-2A affinity) was as effective at alleviating cognitive deficits as olanzapine (high 5HT-2A affinity). 5 Although this finding in itself does not suggest a cognitive advantage of atypical antipsychotics with no affinity for 5HT-2A receptors, Wagner et al did note stronger effects of amisulpride on attention and executive function and suggested that a similar study with higher statistical power might demonstrate an advantage of amisulpride over risperidone. 5 Certainly, the assertion that serotonin activation impairs learning and memory whereas reduced serotonergic function enhances these processes needs reconsideration.…”
Section: Discussionmentioning
confidence: 92%
“…5 Although this finding in itself does not suggest a cognitive advantage of atypical antipsychotics with no affinity for 5HT-2A receptors, Wagner et al did note stronger effects of amisulpride on attention and executive function and suggested that a similar study with higher statistical power might demonstrate an advantage of amisulpride over risperidone. 5 Certainly, the assertion that serotonin activation impairs learning and memory whereas reduced serotonergic function enhances these processes needs reconsideration. 37 In addition, our finding of enhanced social abilities for the low-5HT-2A-affinity group suggests that serotonergic mechanisms are important for successful functioning in a social environment.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations